Methodological instructions to practical classes, independent work and performance of an individual task from the discipline "Marketing effectiveness management" - Larka, Lyudmila (National Technical University "Kharkiv Polytechnic Institute", 2025)
These methodological instructions consist of three parts: instructions for practical classes, instructions for independent work, and instructions for completing an individual task. Instructions for practical lessons are presented in the form of a detailed lesson plan, which allows applicants to focus on the key points of the topic of the practical lesson. Discussion of given topics during practical classes allows students to practice the skills of conducting a scientific debate, justify their own point of view, and listen to constructive criticism. The topics of practical classes correspond to the syllabus of the discipline "Marketing effectiveness management". Instructions for independent work contain tasks for independent implementation and tests, the completion of which allows students to consolidate the material of lectures and practical classes. According to the curriculum for students of the second (master's) level of higher education in the specialty D 5 "Marketing", the individual task of the discipline "Marketing effectiveness management" is a calculation task. The purpose of the calculation task is to assess the effectiveness of using the marketing potential of the enterprise in the context of managing the effectiveness of its marketing activities. In order to fulfill the goal, it is necessary to determine the components of the marketing potential of the researched enterprise, to build a graph-analytical model of the "square of marketing potential" of the enterprise, to determine the efficiency of using the marketing potential of the enterprise, to propose a strategy for managing the marketing potential of the enterprise in the context of managing the marketing activities of the enterprise. Methodical instructions for practical classes, instructions for independent work and instructions for completing an individual task are part of the educational and methodological complex of the discipline.
Keywords: methodological instructions; marketing activities; management; internal marketing algorithm; GAP-analysis; benchmarking analysis; customer loyalty research